Reaching smallholder women with information services and resilience strategies to respond to climate change - Ringler, Claudia; Alvi, Muzna; Birner, Regina; Bosch, Christine; Bryan, Elizabeth; Githuku, Fridah; Meinzen-Dick, Ruth S.; Rwamigisa, Patience B.; Shah, Mansi (International Food Policy Research Institute, 2023)
The project Reaching Smallholder Women with Information Services and Resilience Strategies to Respond to Climate Change aimed to increase the climate resilience of poor women and men farmers in Africa south of the Sahara and South Asia — especially those in Kenya, Uganda, and India — by overcoming the gendered information gap on accessing climate-smart agricultural (CSA) approaches. The project did this through piloting participatory video-based extension on CSA approaches with more than 30,000 farmers in the three countries. The notes in this collection summarize the key methods and findings from the study. It is hoped that they will inspire similar projects and programs that together will help eliminate the gap between rural men and women in resources, agency, and achievement once and for all.